Liquefied Petroleum Gas (LPG) leakage detection and monitoring system - Sitan, Tamil Selvi; Ab Ghafar, Aimi Syamimi (UTHM Publisher, 2018)
A system consists of detection and monitoring system is very common in industrial field. However, this system still very rare in domestic. Detection and monitoring system of Liquefied Petroleum Gas (LPG) is very important in home because it is common to be used at homes. The purpose of this project is to develop Liquefied Petroleum Gas leakage detection and monitoring system. This system consists of two sensing unit, two types of alarm alert and an online monitoring system. Gas sensor is used for gas leakage detection specified to LPG gas only and load cell sensor is used to weigh the gas cylinder. A physical alarm alert using buzzer is installed for gas detection only while non-physical alert alarm which is sending notification and email to user through smartphone are developed to equip the system with Internet of Thing (IoT) technology. This includes notification of both gas leakage and empty gas cylinder. For monitoring purpose, Blynk application is used as the IoT platform because of its user friendliness for both iOS and Android smartphone users. Real-time data is sent through WiFi so that users can monitor their kitchen condition remotely and receive alert for both gas leakage and gas cylinder condition through their smartphones. In conclusion, the proposed LPG leakage detection and monitoring system has been successfully developed and has lower cost compared to existing system on the shelves. This system is suitable for domestic usage and small premise usage.